Crescimento, produção e qualidade do melão produzido sob Lithothamnium - Negreiros, Andréia Mitsa Paiva (2015)
Among the numerous problems in the culture of melon plants, is the dependence of fertilizer inputs. The Lithothamnium (Lit.) is presented as an alternative source of calcium and magnesium. This research studies the growth, yield and quality of melon to the different formulations, doses, method and application intervals (IA) Lit. Three experiments were conducted, two in greenhouse and in the field. In the first experiment cv. melon seeds were used. 'Gladial', planted in plastic containers with 0.5 kg capacity with organic substrate. The treatments were: T1-test .; T2, T3, T4 - Lit. concentrated suspension - SC at doses 10, 20, 30 L / ha, respectively; T5-Nit. amino acid + calcium 5L / ha; T6, T7, T8 - Lit. nanoparticles in the doses 1, 5, 10 kg / ha, respectively; T9-Lit. Powder-micronized, 50 kg / ha and T10-Quantile 10L / ha. The T6 treatment differed statistically by Tukey a 5% probability of other treatments for the variables plant height (PH), fresh weight of shoots (PFPA) and fresh root weight (PFR). In the second experiment the following treatments were used: T1-test .; T2, T3, T4 Lit. nanoparticles; T5, T6, T7 Lit. powder-micronized; T8, T9, T10 Lit. SC, AI 7-7, 10-10, 14-14 DAS, for each formulation, respectively. The results indicated significant differences for IA (14-14 DAS) only for the PSPA and PSR variable, with the best formulations Lit. in nanoparticles and SC for AP variables, PFPA and root length. The experiment III was produced in a commercial area of Dina company, in which the treatments were T1-test. T2, T3 Lit. powder-micronized; T4, T5-Lit SC; T6, T7-Lit nano (FT) and T8, T9-Lit. nano; T10, T11-Lit. SC (Pulv.). The results indicated that the fruits produced showed the oblong fruit shape. All treatments with Lit. were higher than the control for the variable shell thickness. The T6 to T11 treatments differed from the other for the variable firmness, by Scott-Knott test. These are the first data Lit. for melons in Brazilian literature, being necessary experiments with other types of melon. So Lit. provided increment in the evaluated variables and can be used for melons to improve both plant growth as post-harvest fruit quality